Eco-engineered remediation: Microbial and rhizosphere-based strategies for heavy metal detoxification - Arun Karnwal; Gaurav Kumar; Alaa El Din Mahmoud; Joydeep Dutta; Rattandeep Singh; Abdel Rahman Mohammad Said Al-Tawaha; Tabarak Malik (Current Research in Biotechnology)
Heavy metal (HM) contamination significantly threatens ecosystems and human health. This review explores eco-engineered bioremediation strategies, focusing on the pivotal role of rhizosphere-associated microorganisms in detoxifying heavy metals. Rhizobacteria deploy diverse mechanisms—including biosorption, bioaccumulation, biotransformation, and biomineralization—to immobilize or convert toxic metals, with their efficiency strongly influenced by environmental factors such as pH and metal speciation. Plant Growth-Promoting Rhizobacteria (PGPR) further enhance phytoremediation by mitigating metal-induced phytotoxicity and promoting plant resilience under stress. Various scalable approaches, including in-situ and ex-situ remediation techniques, biosorbents, microbial consortia, and genetically engineered microbes (GEMs), show promising potential but raise essential ecological and regulatory concerns. Key challenges such as scalability, environmental variability, and the possible formation of toxic intermediates must be carefully addressed. Advances in omics technologies and a deeper exploration of native microbial communities offer promising avenues to optimize bioremediation outcomes. Moreover, a detailed understanding of plant–microbe interactions and the role of secondary metabolite signalling in the rhizosphere is essential to improve remediation efficiency. Future strategies should prioritize the application of functional genomics, developing bioinoculants tailored to specific environmental conditions, and implementing robust ecological risk assessments for GEMs. This review underscores the need for a multidisciplinary approach- integrating microbial ecology, plant sciences, and environmental engineering- to drive the development of sustainable, effective HM remediation technologies worldwide.